(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Clerodendrum inerme (L.) Gaertn. (Verbenaceae) is very popular among the traditional practitioners in Bangladesh for the treatment of local pain and inflammation, skin diseases, topical burns etc. However, so far no scientific study has been carried out which may support its uses in traditional medicine. In the present study, we evaluated the possible analgesic and anti-inflammatory activities of the ethanol extract of C. inerme for the first time. Analgesic activity was assessed by using acetic acid-induced writhing and heat-induced pain in mice and anti-inflammatory activity using xylene-induced ear edema in mice at the doses of 250 and 500 mg/kg body weight. The extract significantly (P< 0.05) attenuated the acetic acid-induced writhing with the highest activity being observed at 500 mg/kg b.w. (45.83%) comparable to that of diclofenac sodium (57.64%), the standard drug. A significant dosedependent increase (P< 0.05) of the latency period was also observed in hot plate method. In the xylene-induced inflammation assay, the extract showed significant (P<0.05) and dose dependant inhibitory effect on the edema formation. These findings indicate that the extract has significant analgesic and anti-inflammatory activities which support the folkloric claim of this plant and thus it has a great potential as source of natural products-derived drug. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22317 Bangladesh Pharmaceutical Journal 17(1): 62-66, 2014